Repair of cerebrospinal fluid leak during posterior thoracolumbar surgery using paraspinal muscle flap combined with fat graft - Gao, Xianda; Du, Peiyu; Xu, Jiaxin; Sun, Jiayuan; Ding, Wenyuan; Yang, Da-Long (Frontiers in Surgery, 2022)
Objective: This study aimed to propose a novel surgical method via combination of fat graft and paraspinal muscle flap, in order to treat cerebrospinal fluid (CSF) leak during posterior thoracolumbar surgery. The clinical outcomes were also evaluated. Methods: Data of a total of 71 patients who were diagnosed with intraoperative incidental durotomy and CSF leak after posterior thoracolumbar surgery in our hospital form January 2019 to January 2021 were retrospectively collected and analyzed. Among them, 34 and 37 patients were assigned into conventional suturing (CS) group and fat graft and paraspinal muscle flap (FPM) group, respectively. Patients’ demographic and clinical data were compared between the two groups. Results: The average drainage tube time in the FPM group was 3.89±1.17 days, which was shorter than that in the CS group (5.12±1.56, P<0.001). The drainage volume in the FPM group (281.08±284.76 ml) was also smaller than that in the CS group (859.70±553.11 ml, P<0.001). Besides, 15 (44.11%) patients in the CS group complained of postural headache, which was more than that in the FPM group (7 patients, 18.91%). There was a statistically significant difference in postoperative visual analogue scale (VAS) score between the two groups (P=0.013). Two patients underwent revision surgery resulting from incision nonunion and delayed meningeal cyst. Conclusion: Fat graft combined with paraspinal muscle flap showed to be an effective method to repair CSF leak during posterior thoracolumbar surgery. The proposed method significantly reduced postoperative drainage tube time and postoperative drainage volume. . It also decreased the incidence and the degree of postural headache. The proposed method showed satisfactory clinical outcomes, and it is worthy of promotion.